STUDY ON FLARING SYSTEM FOR SOUR GASES IN OIL FIELDS IN INDONESIA - R. Desrina; Supriyadi Supriyadi; Aziz M Lubad; M Mulyono (Testing Center for Oil and Gas LEMIGAS, 2007)
Many of the oil fields in East Java, Indonesia, are known to contain sulfur in amountssufficiently high that the crude oil or the associated gases are considered sour. The sourgases have to be handled accordingly in order to prevent the workers and the surroundingcommunities suffering from the toxic gas.The flaring system for disposing of the sour gases normally applied in oil fields inIndonesia has been evaluated in this study. Flare Stacks typically attempt to convert hydrogensulfide (H2S) in sour gas streams into sulfur dioxide (SO2) and water. The amount ofSO2 emitted does not solely depend on the H2S content of the gas, but also on the internalphysical factors, such as flare gas flow rate, flare gas heat content, flare gas exit velocity,and external factors such as cross wind velocity.This study focuses on the evaluation of the influence of the physical factors, especiallyflare gas flow rate and wind velocity, on SO2 emission. In order to comply with the regulationthe study also attempts to search the Government of Indonesia Regulations which aresuitable for this purpose.